Urban Sensibility of Landscape Structures in Italy General Characteristics and Local Details - Bernardino Romano; Giulio Tamburini (European Regional Science Association (ERSA), 2006)
Recently the conservation policies in Europe are considering the problem of the urban increasing in terms of soil destroyed and ecosystem fragmentation effects. In Italy this phenomena are becoming particularly important if we consider it at national level, but also at regional level. The paper has the goal to show some data relative to the distribution and the impact of urban surfaces on the large landscape national units, comparing the values among the units kind. Moreover will be implemented the data relative to some regional situation (Lazio, Marche, Umbria) of the Italian peninsula for having the indication about different environmental conditions as, for example, coastal areas, mountain areas or hill areas or also flat areas and different morphological structures. These data will be compare with other territorial characteristics, as the protected areas distribution and the biopermeability areas distribution. The knowledge of these information is very important for the planning action because it is possible to obtain, by means particular GIS models, indications about the urban sensibility of the different land parts in the future.
Keywords: 330